Development and evaluation of a web-based learning system for re-conceptualization : basic electric circuits - Yahaya, Nazli (2002)
The aim of this research was to build a web-based learning system utilizing the Rapid Prototyping model as the theoretical framework. This was a means to persuade 18-19 year-old Malaysian university students, to change thier incorrect electrical concepts, for scientific ones. The learning system for reconceptualization was designed by employing the conept-building model of heirarchical cognition. The student population under study consisted of 93 18-19 year old Malaysian electrical engineering undergraduate freshmen in which more than 90% of this population had several misunderstandings in electrical concepts. The instruments used were the preliminary test, system evaluation checklists, the experimental prer and post tests, subjects web-based answers, interviews and observations.Analysis of results showed an increase of 50% of the subjects who assumed the the correct understanding about the battery as a voltage instead of a current generator, and, that current was never lost rather conserved in a circuit